Menumbuhkan Kepedulian Pemuda : Strategi Organisasi 1000 Guru dalam Rekrutmen Relawan Pendidikan - Deandlles Christover; Abdlu Rofik; Janatun Mardiyah (Concept: Journal of Social Humanities and Education, 2024)
The purpose of this study is to determine the strategy of the Youth Organization of 1000 Teachers in Samarinda City in recruiting volunteers so that prospective volunteers who join have an interest in participating directly in helping with educational problems in remote areas and the obstacles faced by the Youth Organization of 1000 Teachers in conducting the recruitment. Youth with its social control function that has an active role in fighting for various values ​​of life that exist in society, the Youth Organization of 1000 Teachers in Samarinda City as an agent of change plays an active role in implementing education, especially for remote, underdeveloped, and border areas in East Kalimantan Province which still need special attention. This study is descriptive qualitative with a focus on describing and describing the strategy of the Youth Organization of 1000 Teachers in Samarinda City in recruiting volunteers so that prospective volunteers have an interest in participating directly in helping with social problems in the field of education, especially in remote areas and the obstacles faced. The data analysis used is the interactive model data analysis proposed by Miles, Huberman, and Saldana, where this data analysis consists of data collection, data condensation, data presentation and drawing conclusions. This study uses secondary data collection techniques by conducting library research and other secondary data sources and conducting direct research in the field to obtain primary data through in-depth interviews. From the results of the study, it shows that the Strategy of the 1000 Teacher Youth Organization in Increasing Volunteer Interest in East Kalimantan Province has been running well so far. This is because the members of the organization in it, both the Chairperson, Secretary, Treasurer and donations, Creative and event Team, Survey and Logistics Team, and the members of the 1000 Teacher Youth Organization management in Samarinda City are able to adapt and be creative in recruiting prospective volunteers.